Debut. A course of russian for international students. Russian-English-French vocabulary - Snegurova, T.; Romanov, Yu.; Paramonova, V. (ТОВ "Форт", 2020)
Vocabulary of the text-book “Debut. A Course of Russian for International Students” is represented. The text-book includes a range of material to give students the essential skills and knowledge they need for Russian reading, speaking, and writing from level A2 (“Russian for beginners”) up to B1 (“Debut 1”) and B2 (“Debut 2”) according to Council of Europe language descriptor. This course is intended for a very wide audience of Russian language learners, pursuing various goals (living and studying in those countries where Russian is spoken; short-term Russian courses; traineeship; language credits, etc.).

Репрезентовано лексику уроків підручника “Debut. A Course of Russian for International Students”, який містить матеріали, що мають на меті формування у студентів знань і навичок російського читання, говоріння та письма від рівня А2 (“Russian for beginners”) до рівня В1 (“Debut 1”) та рівня В2 (“Debut 2”) за мовним дескриптором Ради Європи. Призначено для широкого кола студентів, які вивчають російську мову для різних цілей (проживання та навчання в країнах, де говорять російською; короткострокові курси російської мови, стажування, отримання академічних кредитів з іноземної мови і т. ін.).
Дебют. Курс русского языка для иностранных студентов.Русско-англо-французский словарь
Keywords: Russian vocabulary; English vocabulary; French vocabulary; international students